The affects of pedagogy in literary studies - Lloyd, Christopher, 1987-; Emmett, Hilary (New York, NY : Routledge, 2023)
"The Affects of Pedagogy in Literary Studies considers the ways in which teachers and students are affected by our encounters with literature and other cultural texts in the higher education classroom. The essays consider the range of emotions and affects elicited by teaching settings and practices: those moments when we in the university are caught off-guard and made uncomfortable, or experience joy, anger, boredom, and surprise. Featuring writing by teachers at different stages in their career, institutions, and national or cultural settings, the book is an innovative and necessary addition to both the study of affect, theories of learning and teaching, and the fields of literary and cultural studies"--
Keywords: Literature -- Study and teaching (Higher); Affective education; Teaching -- Psychological aspects; LITERARY CRITICISM / Books & Reading; EDUCATION / Philosophy & Social Aspects; SOCIAL SCIENCE / Anthropology / Cultural